2020
DOI: 10.1002/mawe.201900029
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing mechanical and wear performance of dental composite: A review

Abstract: With environmental concerns, the development of a posterior restorative as a true alternative to dental amalgam is needed. Hence in this regard, the development of dental composites have gained more and more research interest, as they have the advantages of better aesthetic look, better physical, mechanical and tribological properties over the other available dental materials. In this study, the physical, mechanical and wear behavior of dental composite materials have been reviewed. Numerous experimental resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 89 publications
1
9
0
Order By: Relevance
“…Therefore, as compared to dental composite without nanofiller and glass ionomer, that is, DC-O, dental composite with nanofiller and glass ionomer exhibited better performance in all the criteria. This result is in-agreement with various literatures [32,33] in which it was reported that nanofiller and glass ionomer enhanced the physical, mechanical, and wear performance of dental composite. Finally, it can be concluded that despite of more void content and low flexural strength, glass ionomer has shown comparable properties with respect to nanosilica and significant properties with respect to nanoalumina.…”
Section: Ranking Of the Dental Composites On The Basis Of Physical Me...supporting
confidence: 93%
“…Therefore, as compared to dental composite without nanofiller and glass ionomer, that is, DC-O, dental composite with nanofiller and glass ionomer exhibited better performance in all the criteria. This result is in-agreement with various literatures [32,33] in which it was reported that nanofiller and glass ionomer enhanced the physical, mechanical, and wear performance of dental composite. Finally, it can be concluded that despite of more void content and low flexural strength, glass ionomer has shown comparable properties with respect to nanosilica and significant properties with respect to nanoalumina.…”
Section: Ranking Of the Dental Composites On The Basis Of Physical Me...supporting
confidence: 93%
“…However, optimum composition of fillers should be used to obtain optimized physical, mechanical and clinical performance [37]. For comparative investigation of effect of ceramic nanofiller and glass ionomer cement, the most commonly used mechanical characterization methods include compressive strength (CS), flexural strength (FS), diametral tensile strength (DTS), fracture toughness (FT), microhardness (Knoop (KHN) or Vickers (VHN)), wear rate (WR), fatigue and creep [38][39][40].…”
Section: Comparative Analysis Of Mechanical Properties Between Nanofi...mentioning
confidence: 99%
“…Better performance of composite can be achieved by using the concept of nanotechnology. Addition of nanofiller enhanced the mechanical properties of polymer composite 12–14 . The mechanical properties and thermal resistance of WPC was improved by adding nanosilica filler 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Addition of nanofiller enhanced the mechanical properties of polymer composite. [12][13][14] The mechanical properties and thermal resistance of WPC was improved by adding nanosilica filler. 15,16 Biodegradable and biocompatible polymers exhibit "shape recovery property" which allows them to quickly recover their original shape under the environment temperature more than glass transition temperature.…”
mentioning
confidence: 99%